Somatic Anxiety And Cognitive Anxiety Of Football Players: Evidence From Manipuri Women Football Player - Naorem, Sharina; Farooque, Sm; Adhikari, Tanmoy; Adhikari, Tanmoy; Sailo, Lalmanghaisanga (International Journal of Psychosocial Rehabilitation, 2020)
Anxiety is perceived as an emotion that is characterized by anxious feelings, worried thoughts, and physical changes such as elevated blood pressure. Usually, anxiety is considered an unpleasant condition in response to perceived stress about the execution of a task under pressure. Every player is experiencing the different phase of anxiety. The sole aim of this study is to find out the different state of anxiety among the women football players. For the purpose of the study U-17, 21 elite women players were selected from Manipur who had recently played U-17 world Cup. The purposive sampling method were employed. For the analysis of data, descriptive statistics were used to analyse their mean average and the different deviation. To find the mean difference ANOVA were employed. The result shows that higher cognitive anxiety as compare with the somatic and self-confidence. Further the study reveals that lack of confidence among the players which may be the root cause of boosting competition anxiety. The study suggests that to have psychological intervention program is very important to build up player performance.